Positioning the History of Science
VII, 188 p.
Keywords: The present volume, compiled in honor of an outstanding historian of science, physicist and exceptional human being, Sam Schweber, is unique in assembling a broad spectrum of positions on the history of science by some of its leading representatives. Readers will find it illuminating to learn how prominent authors judge the current status and the future perspectives of their field. Students will find this volume helpful as a guide in a fragmented field that continues to be dominated by idiosyncratic expertise and that still lacks a methodical canon. The essays were written in response to our invitation to explicate the views of the authors concerning the state of the history of science today and the issues we felt are related to its future. Although not all the scholars invited to write have contributed an essay, this volume can nevertheless be considered as a rather comprehensive survey of the present state of the history of science. All the papers collected here reflect in one wayor another the strong influence Sam Schweber exerted during the past decades in his gentle way, on the history of science as well as on the lives of many of its protagonists worldwide. All who have had the opportunity of encountering him have benefited from his advice, benevolence, and friendship. Sam Schweber’s intellectual taste, his passion for knowledge, and his erudition are all encompassing. It, therefore, seemed fitting to honor him with a collection of essays of comparable breadth; nothing less would suffice.